Capturing Solvation Effects at a Liquid/Nanoparticle Interface by Ab Initio Molecular Dynamics: Pt201 Immersed in Water. Issue 38 (17th August 2016) - de Morais, Rodrigo Ferreira; Kerber, Torsten; Calle‐Vallejo, Federico; Sautet, Philippe; Loffreda, David
Abstract : Solvation can substantially modify the adsorption properties of heterogeneous catalysts. Although essential for achieving realistic theoretical models, assessing such solvent effects over nanoparticles is challenging from a computational standpoint due to the complexity of those liquid/metal interfaces. This effect is investigated by ab initio molecular dynamics simulations at 350 K of a large platinum nanoparticle immersed in liquid water. The first solvation layer contains twice as much physisorbed water molecules above the terraces, than chemisorbed ones located only at edges and corners. The solvent stabilizes the binding energy of chemisorbates: 66% of the total gain comes from interactions with physisorbed molecules and 34% from the influence of bulk liquid. Abstract : Ab initio molecular dynamics simulations are proposed to investigate the solvation effects at the interface between a platinum nanoparticle (Pt201 ) and liquid water at 350 K. The first solvation layer contains twice as much physisorbed water molecules above the terraces, than chemisorbed ones located only at edges and corners. The solvent stabilizes the binding energy of chemisorbates.